Can standard preferences explain the prices of out-of-the-money S&P 500 put options? - Luca Benzoni; Pierre Collin-Dufresne; Robert S. Goldstein (Federal Reserve Bank of Chicago, 2011)
The 1987 stock market crash occurred with minimal impact on observable economic variables (e.g., consumption), yet dramatically and permanently changed the shape of the implied volatility curve for equity index options. Here, we propose a general equilibrium model that captures many salient features of the U.S. equity and options markets before, during, and after the crash. The representative agent is endowed with Epstein-Zin preferences and the aggregate dividend and consumption processes are driven by a persistent stochastic growth variable that can jump. In reaction to a market crash, the agent updates her beliefs about the distribution of the jump component. We identify a realistic calibration of the model that matches the prices of shortmaturity at-the-money and deep out-of- the-money S&P 500 put options, as well as the prices of individual stock options. Further, the model generates a steep shift in the implied volatility 'smirk' for S&P 500 options after the 1987 crash. This 'regime shift' occurs in spite of a minimal impact on observable macroeconomic fundamentals. Finally, the model's implications are consistent with the empirical properties of dividends, the equity premium, as well as the level and standard deviation of the risk-free rate. Overall, our findings show that it is possible to reconcile the stylized properties of the equity and option markets in the framework of rational expectations, consistent with the notion that these two markets are integrated.
Keywords: G12; G13; 330; Volatility Smile; Volatility Smirk; Implied Volatility; Option Pricing; Portfolio Insurance; Market Risk